Teachers’ perspectives on the use of microlearning TikTok in assessing students’ speaking skill within Merdeka curriculum: An exploratory study - Utami, Ni Luh Kadek Mega; Nur'Aini, Siti; Senowarsito, Senowarsito (EduLite: Journal of English Education, Literature and Culture, 2025)
Merdeka Curriculum frees teachers and students to use any learning media in the teaching and learning process. In this study, the researchers focus on how the microlearning TikTok platform is used to assess speaking skills. This study aims to discover the challenges faced by English teachers, the solutions to overcome them, and the benefits of using Microlearning on the TikTok platform to assess students’ speaking skills. This study is under a qualitative exploratory study with descriptive qualitative analysis. The data was obtained through participants who were recruited using purposive sampling. Three English teachers from one high school in Denpasar participated in this study. Data were collected through observation, a questionnaire, and in-depth interviews. The findings show the challenges overcome by English teachers in assessing students’ speaking skills using microlearning TikTok derive from the external factors like students, curriculum, and time. However, the teachers give alternative solutions for the teachers who face the same challenges, such as assessing students directly (face to face) in the class, preparing, and adapting to the spread of technology and curriculum. In addition, the benefits of TikTok based on teachers’ perspectives could increase students’ speaking skills, such as grammar, vocabulary, pronunciation, fluency, and comprehension. Its implications allow future studies for researchers who are interested in Microlearning TikTok, especially for using it as an assessment media. This study can be a reflection of the English teachers in the implementation of the Merdeka curriculum.